Up-conversion luminescence properties of lanthanide-doped LuF3 with different morphologies synthesized via a facile ionothermal process. Issue 10 (14th March 2015) - Yu, Xue; Bian, Wenjuan; Wang, Ting; Zhou, Dacheng; Qiu, Jianbei; Xu, Xuhui
<x xml:space="preserve">Abstract</x> Up-conversion (UC) crystals of lanthanide-doped LuF3 with different morphologies (nanoparticles, shuttle- and litchi-like microcrystals) have been synthesized via a facile ionothermal method.